3Dmol.js: molecular visualization with WebGL - Rego, Nicholas; Koes, David (Bioinformatics, 2015)
3Dmol.js is a modern, object-oriented JavaScript library that uses the latest web technologies to provide interactive, hardware-accelerated three-dimensional representations of molecular data without the need to install browser plugins or Java. 3Dmol.js provides a full featured API for developers as well as a straightforward declarative interface that lets users easily share and embed molecular data in websites. Availability and implementation: 3Dmol.js is distributed under the permissive BSD open source license. Source code and documentation can be found at http://3Dmol.csb.pitt.edu Contact:  dkoes@pitt.edu